1990
DOI: 10.1111/j.1365-2249.1990.tb06451.x
|View full text |Cite
|
Sign up to set email alerts
|

Cells and mediators which participate in immunoglobulin synthesis by human mononuclear cells. II. The mechanism of null cell participation in immunoglobulin synthesis and secretion by B cells

Abstract: SUMMARYImmunoglobulins were synthesized and secreted by human B cells cultured with T cells with receptors for FcM (TM) helper cells, monocytes, null cells and PWM for 7 days. Immunoglobulin synthesis did not take place if the null cells were omitted from the cultures irrespective ofthe duration ofthe culture period. Null cells incorporated into the cultures at only 25% of their optimal concentration did not affect immunoglobulin synthesis markedly by the cultured B cells. However, the number of B cells in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1990
1990
1992
1992

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…In previous investigations (Richter & Jodouin, 1985;Richter et al, 1990) it was demonstrated that the null lymphocytes are obligatory participants in immunoglobulin synthesis by cultured B cells, as are the TM helper cells, monocytes and PWM. However, the mechanism of null cell participation was not determined.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous investigations (Richter & Jodouin, 1985;Richter et al, 1990) it was demonstrated that the null lymphocytes are obligatory participants in immunoglobulin synthesis by cultured B cells, as are the TM helper cells, monocytes and PWM. However, the mechanism of null cell participation was not determined.…”
Section: Discussionmentioning
confidence: 99%
“…The methods used for the isolation of the MNC from whole blood of healthy volunteers, the fractionation ofthe MNC into T and non-T cells by rosetting with sheep erythrocytes, the formation ofthe EAG indicator cells, the separation ofthe non-T cells into the null cells and the B cells by rosetting the non-T cells with EAG, the isolation of the TM helper cells, the elimination of monocytes by carbonyl iron phagocytosis, the immunofluorescent assay to detect immunoglobulin-synthesizing cells, and the ELISA to determine IgG and IgM secreted by the cultured cells, have all been described in previous publications (Richter & Jodouin, 1985;Richter et al, 1990).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation